Leader-member exchange, work engagement, job standardisation and innovative work behaviour in Malaysian public sector - Intan Wirdati Suhaimii; Siti Aisyah Panatik, supervisor; Sekolah Perniagaan Antarabangsa Azman Hashim (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah) - Universiti Teknologi Malaysia, 2018